A Descriptive Study of the Kentucky Correctional Industries Program - Castellano, Thomas C. (2000)
This bulletin addresses the topic of correctional industry programs. These programs are common across the United States and Europe, and research suggests that they may hold promise for helping accomplish correctional goals. However, correctional industry programs have not been adequately evaluated in the literature